2020
DOI: 10.1021/acsami.0c02495
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible In Situ Polymerization of Multipurpose Polyacrylamide-Based Hydrogels on Skin via Silver Ion Catalyzation

Abstract: Free radical polymerization is a mature method and can be used for preparing multifunctional hydrogels by simply changing the commercial monomers, but the harsh and timeconsuming initiation conditions restrict its injectable ability, which further limits its application in the biomedical field. Though some catalysts can be used to accelerate the polymerization, their application is restrained by the biotoxicity. Hence, finding a biocompatible catalyzer for in situ free radical polymerization of hydrogels has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 57 publications
1
46
0
2
Order By: Relevance
“…As one of the most popular approaches, copolymerization can not only control the crosslink density and ion contents in the hydrogel network by directly tuning the ratios among different monomers, 66 but is also useful in modifying the special functional groups on the hydrogel backbones and forming covalent crosslinking and physical interactions among chains through graing. 72,74 However, it is time-consuming and requires strict controls for preparation, 154 and lacks mechanical and conductive stability when conductive hydrogels are prepared. 23 Compared to copolymerization, doping can also be employed to modify the mechanical and conductive properties by controlling the amount of dopants.…”
Section: Perspective and Discussionmentioning
confidence: 99%
“…As one of the most popular approaches, copolymerization can not only control the crosslink density and ion contents in the hydrogel network by directly tuning the ratios among different monomers, 66 but is also useful in modifying the special functional groups on the hydrogel backbones and forming covalent crosslinking and physical interactions among chains through graing. 72,74 However, it is time-consuming and requires strict controls for preparation, 154 and lacks mechanical and conductive stability when conductive hydrogels are prepared. 23 Compared to copolymerization, doping can also be employed to modify the mechanical and conductive properties by controlling the amount of dopants.…”
Section: Perspective and Discussionmentioning
confidence: 99%
“…In situ, PAM/SA/Ag hydrogels were prepared by using silver ions in the presence of ammonium persulfate to catalyze free radical polymerization. Histocompatibility experiment results showed that the hydrogels showed higher expression of CD31 and VEGF, which are related to angiogenesis in wound healing [ 65 ].…”
Section: Preparation Methods Of Hydrogels With a Promising Treatment For Wound Healingmentioning
confidence: 99%
“…For example, metal ions (e.g., Fe 3+ , Cu 2+ , Al 3+ ) can form reversible coordination bonds with carboxyl groups, which serve as sacrificial bonds to effectively dissipate energy for enhancing the mechanical properties . Additionally, metal ions such as Ag + could not only endow the hydrogel with excellent electronic and antibacterial properties, , but also activate ammonium persulfate (APS) through electron transfer to produce a sulfate radical (SO 4 ), which can lead to the rapid polymerization of vinyl monomers without external introduction of energy. Although the hydrogel sensors can realize various excellent properties mentioned above, the interfacial delamination between the sensor and the skin during long-term contact may lead to the instability of signal detection . Furthermore, the assistance of adhesive tape on the human skins to ensure long-term signal detection stability may bring operational complexity .…”
Section: Introductionmentioning
confidence: 99%